Disease activity and treatment in patients with juvenile idiopathic arthritis before transfer to adult care: the first survey in China - Luo, Xiya; Luo, Xiwen; Luo, Qiang; Tang, Xuemei (Frontiers in Pediatrics, 2025)
ObjectivesTo analyze disease activity and treatment in patients with juvenile idiopathic arthritis (JIA) before transfer to adult care.MethodsWe retrospectively collected the clinical data of 230 JIA patients (range 14–18 years) in our center from January 2013 to December 2022. We evaluated the clinical features, disease activity, and medication use across various JIA subtypes.Results230 patients with JIA were included, and 144 (63%) were male. The distribution of JIA subtypes was dominated by enthesitis-related arthritis (32%), polyarthritis (31%), systemic JIA (27%), and oligoarthritis (10%). Disease activity assessment showed that 87 JIA (38%) were in active disease; while 143 JIA (62%) were in inactive disease, of which 59 patients achieved clinical remission on medicine and 13 patients achieved clinical remission off medicine. Conventional synthetic disease-modifying anti-rheumatic drugs were used in 83% of JIA patients, and biologics in 56%. Clinical characteristics and medication use differed between different subtypes of JIA. The oligoarthritis group had earlier disease onset (P = 0.020) and longer disease duration (P = 0.009) compared to other subtypes. Patients in the RF-positive polyarthritis group had a significantly lower rate of disease inactivity (39%, P = 0.004) than the other subtypes, and a relatively lower proportion of patients achieved clinical remission on medication or discontinuation of medication (18%, P = 0.024).ConclusionsSome JIA patients were still in active disease before transfer to adult clinics, failing to achieve clinical remission and discontinuation of medication, and required continued treatment. Patients in the RF-positive polyarthritis group were less likely to achieve clinical remission.